Gambaran Komposisi Makanan Siswa SMA pada Masa Pandemi Covid-19 - Patri Cia Yeremia; Riri Novayelinda; Yufitriana Amir (HEALTH CARE: JURNAL KESEHATAN, 2023)
Introduction: Food composition can affect a person's nutritional status, lack of food composition, both in quantity and quality, at each age can cause disturbances in energy production. Every individual needs a healthy and balanced diet to maintain and support smooth activities. This study aims to describe the composition of daily food and the composition of fast food in high school students. Methods: This study uses a simple descriptive. This research was conducted at SMA Negeri 4 Pekanbaru with 89 samples. The measuring instrument used is a questionnaire adapted from the FFQ and distributed using the zoho form. The analysis used is univariate analysis with frequency distribution. Results: Distribution of research results with demographic data on the characteristics of the respondents, namely age and gender, and 46 people (51.7%). The highest gender was female, with 56 respondents (62.9%), The results showed that 37 respondents (41.6%) consumed daily food in the frequent category with a complete arrangement and 44 respondents (44.9%) consumed fast food. serving with the frequent category and there were no students who never consumed fast food. Conclusion: Based on the results of this study, the researchers concluded that the composition of the respondent's daily and fast food in frequent conditions could affect a person's nutritional status.